Peran Generasi Muda Dalam Menghadapi Ancaman Pertanian Indonesia: The Role of the Young Generation in Facing the Threats to Indonesian Agriculture - Purnama, Zapi; Rozaki, Zuhud; Retno, Retno; Amnah, Cantika Wira (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Agriculture and plantations are important sectors that contribute to food security, employment, and national economic growth. However, this sector also faces various challenges, such as food imports, low productivity, and global competition. The younger generation has an important role to play in overcoming these challenges. The younger generation has the advantage of creativity, innovation, and high enthusiasm. They can utilize these advantages to develop Indonesian agriculture and plantations to be more modern, sustainable, and able to meet national food needs.Here are some specific roles of the younger generation in agriculture and plantations, First, Increasing productivity.The younger generation can play a role in increasing agricultural and plantation productivity by applying the right agricultural technology. The right agricultural technology can help farmers to increase crop yields without damaging the environment.And the second is to increase added value.The younger generation can also play a role in increasing the added value of agriculture and plantations. The added value can be increased by developing high-value derivative products.Third, increasing competitiveness. The younger generation can play a role in improving the competitiveness of Indonesian agriculture and plantations in the global market. The young generation can encourage farmers to implement sustainable agricultural practices, such as organic farming and integrated farming.And the last is to become a bridge between farmers and the government. With the active role of the younger generation, Indonesian agriculture and plantations can become more modern, sustainable, and able to meet national food needs. The younger generation needs to be encouraged to take part in the agriculture and plantation sector, because they are the key to the future of this sector.